Spectrum-energy Correlations in GRBs: Update, Reliability, and the Long/Short Dichotomy. (29th March 2018) - Zhang, Z. B.; Zhang, C. T.; Zhao, Y. X.; Luo, J. J.; Jiang, L. Y.; Wang, X. L.; Han, X. L.; Terheide, R. K.
Abstract: Spectrum-energy correlations of peak energy with total prompt γ -ray emission energies, namely E p, i − E iso, E p, i − E γ, and E p, i − L p, had been studied for long gamma-ray bursts (GRBs) previously by many authors. These energy correlations were proposed to measure the universe and classify GRBs as useful probes. However, most of these relations were built by non- Swift bursts. The spectrum-energy correlations of short bursts have not been systematically established yet; in particular, how the newly found GRB170817A matches these energy relations is unknown to date. We will first refresh the three spectrum-energy relations of Swift /BAT and Fermi /GBM long bursts and build the corresponding relations of short bursts. Then, we confirm whether they are commonly available as a discriminator of short and long GRBs. Some potential violators to these relations will be investigated. Combining with the plane of peak energy versus fluence, we select 31 short and 252 long GRBs with well-measured peak energy and redshift to study the issue of GRB classifications connected with the above energy relations statistically. We find that the three energy relations do exist in our new GRB samples and they are marginally consistent with some previous results. We report for the first time that short GRBs hold the three corresponding energy relations having the consistent power-law indices with long GRBs. It is found that these energy relations can be adopted to discriminate GRBs successfully if they are put in the peak energy versus fluence plane. Excitingly, we point out that GRB090510 matches the energy relations of E p, i − E iso and E p, i − L p, but violates the E p, i − E γ relation. More excitingly, we find that GRB170817A is an outlier to all the three energy correlations.